Consensus statements for evaluation and nonpharmacological Management of Psoriatic Arthritis in UAE. (9th June 2022) - Alnaqbi, Khalid A.; Hannawi, Suad; Namas, Rajaie; Alshehhi, Waleed; Badsha, Humeira; Al‐Saleh, Jamal
Abstract: Objective: Psoriatic arthritis (PsA), a chronic inflammatory arthropathy, is often underdiagnosed in Middle Eastern countries, substantially impacting the treatment of affected individuals. This article aims to highlight current unmet clinical needs and provide consensus recommendations for region‐specific evaluation methods and nonpharmacological therapies in the United Arab Emirates (UAE). Method: An extensive literature review was conducted, focusing especially on global and regional guidelines for the evaluation and treatment of PsA. These form the basis of the consensus statements formulated. Additionally, an expert panel of key opinion leaders from the UAE reviewed these guidelines and available literature at an advisory board meeting to identify unmet needs, bridge clinical gaps in the UAE, and develop consensus statements for the evaluation and treatment of PsA. Result: The consensus statements were developed based on overarching principles for the management of PsA, evaluation of patients with PsA, and nonpharmacological approaches for the management of PsA. The overarching principles included adopting a targeted, multidisciplinary approach, along with collaboration between rheumatologists and dermatologists in cases of clinically significant skin involvement. The panel also highlighted the value of composite disease severity measures for characterizing clinical manifestations of PsA. In terms of nonpharmacological management approaches, lifestyle modification (comprising dietary change, exercise, and cessation of smoking) and psychotherapy were recommended. Conclusion: The consensus statements will aid healthcare professionals in clinical decision‐making in the context of PsA.